Determinants of mobile commerce services adoption by Malaysian users - Zurina Patrick; Chin, Shu Qi; Alesia Sigang Gugkang; Geoffrey Harvey Tanakinjal (Human Resource Management Academic Research Society (HRMARS), 2022)
This study aims to determine the factors that influence mobile commerce (m-commerce) services among Malaysian users. The independent variables of this study are perceived usefulness (PU), perceived ease of use (PEoU), perceived trust (PT), and perceived self-efficacy (PSE) while the dependent variable is the adoption of m-commerce services (A). This study employs a quantitative, cross-sectional methodology for its research design. An online survey questionnaire was employed to collect data and yield 200 responses. The findings discovered that PU, PEoU, and PSE significantly influenced the adoption of m-commerce services. This research can provide essential information to companies involved in m-commerce to continuously focus on improving the usefulness of the system, ease of use (i.e., access and usability), and user self-efficacy to rise the adoption of m-commerce in Malaysia. The findings also contributed in terms of allowing researchers to understand the factors that can contribute to the intention to use m-commerce, particularly in the Malaysian context.